The Influence The Influence of Price Perception, Electronic word of mouth (e-WOM), and Product Quality on Purchasing Decisions for Culinary MSME Products in Generation Z in Bangkalan - liling listyawati; Alfariza Ramdini Rahmawati; andry herawati (CV. ITTC INDONESIA, 2026)
The primary objective of this study is to analyze the contributions of price perception, electronic word-of-mouth (e-WOM), and product quality to the purchasing decisions regarding culinary MSME products among Generation Z in Bangkalan Regency. The study employs a descriptive quantitative approach using a survey method with a sample of 100 Generation Z respondents selected via purposive sampling. Data were collected using a 20-item questionnaire covering four operational variables and analyzed through multiple linear regression. Instrument testing confirmed the validity of all items, with calculated r-coefficients (0.785–0.897) consistently exceeding the critical r-table value (0.197). Internal consistency was also established, with Cronbach’s Alpha values ​​ranging from 0.907 to 0.921. Partial regression results indicate that price perception has a positive and significant impact on purchasing decisions (B=0.283; t=4.166; p<0.001). Similarly, e-WOM (B=0.342; t=4.581; p<0.001) and product quality (B=0.434; t=5.619; p<0.001) were found to exert positive and significant influences. Simultaneously, the combination of these three predictors significantly influenced the dependent variable (F=72.005; p<0.001). The Adjusted R-Square value of 0.683 indicates that 68.3% of the variation in purchasing decisions is explained by the independent variables under study, while the remaining 31.7% is attributed to external factors outside the model. Product quality emerged as the most dominant determinant.